2011
DOI: 10.1016/j.clinph.2011.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to mental effort and test???retest reliability of heart rate variability measures in healthy seniors

Abstract: Objectives To determine 1) whether heart rate variability (HRV) was a sensitive and reliable measure in mental effort tasks carried out by healthy seniors and 2) whether non-linear approaches to HRV analysis, in addition to traditional time and frequency domain approaches were useful to study such effects. Methods Forty healthy seniors performed two visual working memory tasks requiring different levels of mental effort, while ECG was recorded. They underwent the same tasks and recordings two weeks later. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
72
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 71 publications
(74 reference statements)
13
72
0
1
Order By: Relevance
“…The ratio of PSD of the pupillary signal within Low and High frequency bands was significantly lower under load on memory condition compared to the control condition; but it did not differ in the luminance conditions. This result is in line with previous studies on the influence of mental workload on heart rate variability showing a greater increase of LF activity compared to HF activity (Durantin et al, 2014;Mizuno et al, 2011;Mukherjee et al, 2011). Nevertheless, note the difference between the frequency bands used in this study compared to the standardized bands used in heart rate variability studies.…”
Section: Effects Of Load On Memory and Luminance Factors On The Lf/hfsupporting
confidence: 92%
See 1 more Smart Citation
“…The ratio of PSD of the pupillary signal within Low and High frequency bands was significantly lower under load on memory condition compared to the control condition; but it did not differ in the luminance conditions. This result is in line with previous studies on the influence of mental workload on heart rate variability showing a greater increase of LF activity compared to HF activity (Durantin et al, 2014;Mizuno et al, 2011;Mukherjee et al, 2011). Nevertheless, note the difference between the frequency bands used in this study compared to the standardized bands used in heart rate variability studies.…”
Section: Effects Of Load On Memory and Luminance Factors On The Lf/hfsupporting
confidence: 92%
“…Since the proposition of Pagani et al (1986), the ratio of cardiac signal powers within LF and HF bands, referred as LF/HF or LH ratio, although controversial (Billman, 2013), is often used to measure the sympatho-vagal balance. Some researchers reported an increase in LF/HF ratio induced by mental effort (Durantin et al, 2014;Mizuno et al, 2011;Mukherjee et al, 2011). Since LF/HF ratios in these studies were greater than 1, this increase could be interpreted as a greater increase in the LF band compared with the HF band.…”
Section: Introductionmentioning
confidence: 90%
“…Activation of the ANS has been reported to occur during cognitive testing involving abilities such as attention, memory and executive function (Hansen et al, 2003;Moses et al, 2007;Mukherjee et al, 2011;Redondo et Del Valle-Inclan, 1992). A link between cognitive function and the ANS is also strongly supported by neuroimaging studies which have shown an activation of the prefrontal cortex during both periods of increased cognitive function and ANS stimulation (Chambers et al, 2006;Chikazoe et al, 2007;Garavan et al, 1999;Gianaros et al, 2004;Konishi et al, 1999;Lane et al, 2001;Lane et al, 2009;Thayer et al, 2009).…”
Section: Introductionmentioning
confidence: 68%
“…This is an important research question, as increases in mental fatigue, amotivational states, and insufficient recruitment of effort have been observed in a variety of clinical conditions, including depression (Cohen et al, 1982;Hammar et al, 2003;Hammar et al, 2011), mild traumatic brain injury (Stulemeijer et al, 2007;Stulemeijer et al, 2006), post-traumatic stress disorder (Shalev et al, 1990), attention deficit hyperactivity disorder (Egeland et al, 2010), and chronic fatigue syndrome (Lawrie et al, 1997;Wallman and Sacco, 2007). Such mental fatigue can produce physiological effects on the body (Mukherjee et al, 2011;Wright et al, 2003), negatively influence performance on unrelated cognitive processes (Wright et al, 2008), and time to recuperate is required following high cognitive effort (Barnes et al, 2009;Smit et al, 2004). The use of stimulants such as amphetamine and caffeine is a common strategy to overcome the mental fatigue associated with high attentional costs, such as sustained highway driving or university lecture attendance (Peeling and Dawson, 2007;Silber et al, 2006), although the extent of their beneficial effect is unclear (de Wit et al, 2002;Drummer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%